Interação genótipo x ambiente e adaptabilidade e estabilidade de híbridos de melão Galia - Santos Júnior, Haroldo (Universidade Federal Rural do Semi-Árido, 2007)
The diversity of environment existent in Rio Grande do Norte due to the different climate conditions and soil can interfere in the adaptability, stability and consequently, in the development of the culture of the melon plant, with reflexes in the productivity and quality of fruits, once those characteristics are influenced directly by the correlation between genotype and environments. The objectives of this work were to verify the importance of the parts simple and complex of the genotype x environment interaction and to evaluate the adaptability and stability of Galia melon hybrid. Nine Galia melon hybrids were tested (GPS 400, DRG 1531, DRG 1537, Solarbel, Solar King, Galileu, Supra, Num 1502 e Arava) in twelve environments of the Rio Grande Norte State (MO-00, MO-01, MO-02, BA-00, BA-01, BA-02, AS-00, AS-01, AS-02, AR-00, AR-01, AR-02) in the period from 2000, 2001 and 2002. The tests were conducted in randomized blocks with three replications. Data were submitted to the analysis of variance individually and jointly and the statistical methods Toler, Wrick and AMMI (Additive Main effect and Multiplicative Interaction) were used to study the adaptability and stability. The complex part is responsible for most of the genotype x environment interaction for the yield and content of solids soluble of fruits. The environments associated with Mossoró and Assu are the most suitable for evaluation of melon Galia. For being stable, productive and to have elevated content of soluble solids, the hybrid DRG 1537 is the most promising for the cultivation in Agripole Mossoró-Assu
Genotypic x environment interaction and adaptability and stability of Galia melon hybrids
Keywords: Cucumis melo; Genotype x environmental interaction; Evaluation of cultivars; Cucumis melo; Interação genótipos x ambientes; Avaliação de cultivares; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA